How to break a dragon's heart - Cowell, Cressida (Cowell, Cressida. How to train your dragon, 2012)
Hiccup, stranded with Toothless on the Beach of the Broken Heart and being hunted by an old enemy, faces Ug the Uglithug, Berserks, and Scarers and tries to save Fishlegs from the Beast.